Effect of Combined Electroacupuncture and Selegiline Treatment in Alzheimer’s Disease: An Animal Model - Cai, Mudan; Yang, Eun Jin (Frontiers in Pharmacology, 2020)
The complexity of pathological mechanisms in Alzheimer’s disease (AD) pose significant challenges to the development of corresponding drugs. Symptom-specific pharmacological interventions and alternative treatments provide promising treatment possibilities. Therefore, we considered a combination of selegiline (SEL) and electroacupuncture (EA). We used an animal model with AD to investigate the effect of a combination of these treatments on cognitive function. 5XFAD mice received a week of SEL treatment and 2 weeks of EA. Novel object recognition and Y-maze tests were subsequently performed to assess their cognitive functions. To determine the molecular action of the combination treatment, Western blots, Aβ1-42 enzyme-linked immunosorbent assays (ELISA), and micro-positron-emission tomography were also performed to assess pathological markers and processes. The results were assessed based on the difference between untreated transgenic, SEL-treated, and SEL- and EA-treated groups of mice. Mice in the combined treatment group demonstrated significantly better cognitive functions, regulated autophagy dysfunction, and lesser neuroinflammation than the comparative groups. In addition, mice treated with a combination of SEL and EA did not demonstrate a direct modulation of insoluble Aβ but did demonstrate greater glucose metabolism. Our findings demonstrated that SEL combined with EA treatment was associated with better cognitive functioning due to inhibition of neuroinflammation and increase of glucose metabolism relative to the comparative groups in a mouse model with AD.